Risk of haematopoietic cancer in patients with inflammatory bowel disease. Issue 5 (14th April 2005) - Askling, J; Brandt, L; Lapidus, A; Karlén, P; Björkholm, M; Löfberg, R; Ekbom, A
Abstract : Background and aims: Several chronic inflammatory conditions are associated with an increased risk of lymphoma. Whether this applies to inflammatory bowel disease (IBD) is still unclear but of paramount interest, particularly in the safety evaluation of newer immunosuppressive drugs. Reports also indicate a possible increase in the risk of leukaemia in IBD. We therefore assessed the risk of haematopoietic cancers in a large cohort of patients with IBD. Subjects and methods: We performed a population based cohort study using prospectively recorded data, including 47 679 Swedish patients with Crohn's disease (CD) or ulcerative colitis (UC) assembled from regional cohorts of IBD from 1955 to 1990 (n = 8028) and from the Inpatient Register of 1964–2000 (n = 45 060), with follow up until 2001. Relative risks were expressed as standardised incidence ratios (SIR). Results: Overall, we observed 264 haematopoietic cancers during follow up, which corresponded to a borderline significant 20% increased risk in both UC and CD. In UC, lymphomas occurred as expected (SIR 1.0, n = 87) but myeloid leukaemia occurred significantly more often than expected (SIR 1.8, n = 32). In CD, there was a borderline significant increased lymphoma risk (SIR 1.3, n = 65), essentially confined to the first years of follow up. Proxy markers of disease activity had little impact on lymphoma risk. Conclusion: On average, patients with IBD have a marginally increased risk of haematopoietic cancer. In UC, this is accounted for by an excess of myeloid leukaemia. In CD, a modest short term increase in the risk of lymphoma of unknown significance cannot be excluded but any long term risk increase seems unlikely.